THE PROFESSION'S RESPONSIBILITY IN ATTRACTING STUDENTS. - Perry, Kenneth W. (The Accounting Review, 1959)
Abstract According to a recent issue of "The Occupational Outlook Handbook" the number of students graduating from college each year in the field of accountancy declined between the years 1950 and 1954 by nearly 50 per cent. Paradoxically the need for qualified accountants has never been greater than at the present time. With demand far exceeding supply the prospect of this situation continuing, and even worsening, should give cause for deep concern and even alarm. The fulfillment of this responsibility calls for a merger of the academic and practical. This need has been evidenced by the receipt during the past few months of hundreds of requests not only for "Young Eyes on Accounting," the career pamphlet published by the Association of International Accountants in cooperation with the American Institute of Certified Public Accountants and the Institute of Internal Auditors, but also by the desire expressed by high school faculty members to be placed on the Association's mailing list for any subsequent mailing of material of this kind. The high schools are endeavoring to do the best job possible.